Analyzing GDPR compliance through the lens of privacy policy - Mohan, Jayashree; Wasserman, Melissa; Chidambaram, Vijay (Poly workshop at VLDB 2019, 2019)
With the arrival of the European Union’s General Data Protection Regulation (GDPR), several companies are making significant changes to their systems to achieve compliance. The changes range from modifying privacy policies to redesigning systems which process personal data. Privacy policy is the main medium of information dissemination between the data controller and the users. This work analyzes the privacy policies of large-scaled cloud services which seek to be GDPR compliant. We show that many services that claim compliance today do not have clear and concise privacy policies. We identify several points in the privacy policies which potentially indicate non-compliance; we term these GDPR dark patterns. We identify GDPR dark patterns in ten large-scale cloud services. Based on our analysis, we propose seven best practices for crafting GDPR privacy policies.